The Development of Cost Structure for High Speed Hard Turning - Adesta, Erry Yulian Triblas; Riza, Muhammad; Al Hazza, Muataz Hazza Faizi; ., Rosehan (ILRAM Publisher, 2008)
High speed hard turning is a new approach that attracts manufacturing firms due to its several advantages, especially for its economical aspects. A development towards a new technological approach shall usually be followed by its economic justification. One of the most effective tools to carry out an economic justification is by development of a cost structure. It may be regarded as an effective tool for decreasing the cost of uncertainty which is usually associated with new technologies. In machining process such as turning, there are many factors that affect the cost. This paper discusses two of these factors which have the higher effect on the high speed hard turning cost. Firstly, the machining cycle time which may be regarded as the most important factor that affect the cost because of its direct relationship with machine cost rate. Secondly, the tool life which is the element that affected by different cutting parameter (feed, depth of cut, cutting speed, work piece material, and tool material). The objective of this research is to highlight these two important factors and the need for developing a generic cost structure for high speed hard turning. These relationships were studied by simulating the machining time for high speed hard turning using Mathlab Simulink® allowing the operator and the manufacturer to calculate rapidly the critical values of machining time as well as helping them in determining the optimum parameters that gives the best results in high speed hard turning.